Heritage Tourism and its Impact on Livelihood: A Study on Heritage Site - Duwadi, Pampha (Rural Development Journal, 2024)
This study aims to investigate the complex relationship between heritage tourism and its impacts on social, cultural, and economic aspects of people's livelihood in the study area. This research is conducted in Changunarayan 4, Bhaktapur. The nature of the study is qualitative. Using Purposive Sampling method, research process is carried out in total 40 households involving in tourism business. This study unveiled positive impacts, including cultural revitalization and preservation, social identity development, and unity. However, it also identified negative effects such as cultural standardization, commercialization, and challenges like cultural clash and littering.